GSM : Architecture, Protocols and Services. - Eberspcher, Jrg (John Wiley & Sons, 2009)
With around 3 billion subscribers, GSM is the world's most commonly used technology for wireless communication. Providing an overview of the innovations that have fuelled this phenomena, GSM: Architecture, Protocols and Services, Third Edition offers a clear introduction to the field of cellular systems. Special emphasis is placed on system architecture and protocol aspects, and topics range from addressing concepts through mobility management to network management. This third edition contains around 25% new and reworked material and has been thoroughly updated to encompass recent advances and.